2018
DOI: 10.1089/fpd.2017.2345
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Genes and Antimicrobial Resistance inEscherichia colifrom Cheese Made from Unpasteurized Milk in Brazil

Abstract: Cow raw milk cheese is widely eaten in Brazil. These products may be contaminated with pathogenic bacteria. In this work, we investigated the presence of Escherichia coli in raw milk cheese from different States in Brazil. From 147 "Minas" cheese samples, 28 cheeses were positive for E. coli. Among 39 E. coli isolates of the cheeses, one was positive for eae and negative for bpfA and efa1/lifA using PCR, and so was classified as atypical Enteropathogenic E. coli (aEPEC). Two other isolates were positive for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…The illegality of these products is associated with the lack of official inspection service and sanitary surveillance. Minas Frescal is one of the most consumed in Brazil and, because it is produced and marketed fresh without maturation and is a very high moisture cheese (46 to 55%), it offers ideal conditions for the multiplication and maintenance of pathogenic microorganisms (de Campos et al, 2018).…”
Section: Short Communicationmentioning
confidence: 99%
“…The illegality of these products is associated with the lack of official inspection service and sanitary surveillance. Minas Frescal is one of the most consumed in Brazil and, because it is produced and marketed fresh without maturation and is a very high moisture cheese (46 to 55%), it offers ideal conditions for the multiplication and maintenance of pathogenic microorganisms (de Campos et al, 2018).…”
Section: Short Communicationmentioning
confidence: 99%
“…Finally, we sought to describe the antibiotic risk that may arise from foodborne pathogens in IFM. This is because pathogens that are resistant to antibiotics, especially the multidrug-resistant pathogens, present major public health and economic concerns worldwide [8]. We identified only three out of the 18 studies that went further to characterize the antibiotic profile of pathogens isolated from IFM.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a large proportion of IFM is artisanal, and in most cases, the processing lacks the level of sophistication to implement necessary food safety control measures to ensure high level of food safety [7]. Most of the IFM is processed from unpasteurized raw milk, which has been shown to harbor foodborne pathogens [8]. Possible contamination with foodborne pathogens from milk handlers can also occur due to the lack of adequate food safety control measures within the milk processing environment [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, none of the SAC samples were positive for any category of pathogenic E. coli. In contrast, some studies have found diarrheagenic E. coli in samples of artisanal cheeses (Paneto et al, 2007;Marozzi et al, 2016;de Campos et al, 2018;Parussolo et al, 2019), but all have made an association between the microbiological culture and the use of the PCR technique, suggesting that the food matrix may interfere in the direct detection of these pathogenic strains.…”
Section: Categorymentioning
confidence: 97%